Bibliometric Analysis of Post-Occupancy Evaluation (POE): Current Status, Development, and Future Research Directions - Wan Mustaffa, Wan Nor Faezah; Che Ani, Adi Irfan; Hussain, Afifuddin Husairi (International Journal of Sustainable Construction Engineering and Technology, 2022)
The application of post-occupancy evaluation (POE) has increased recently, owing to the methodology's ability to improve building performance. However, the procedures employed vary depending on the building's suitability and category. Therefore, this study aims to provide a comprehensive survey to explore the state-of-the-art POE research. Bibliometric analysis was used to retrieve 381 POE publications from the Scopus database between 1979 and 2020. VOSviewer software was applied for the visualization and scientific mapping of literature. The study helps researchers understand by offering comprehensive data about the most literate nation contributions, publications' significant sources, and devoted authors to POE publications. The findings revealed that the United States, the United Kingdom, and China had rendered the three most literature contributions; Building Research and Information were the top publication's significant source titles, and Hassanain, M.A. is incredibly devoted to POE publication. Research hotspots in the POE focus on building performance, architectural design, and sustainable development. The primary themes in POE concentrate on comfort, sustainability, performance, design and criteria. Future research should emphasize that POE is used on heritage buildings to ensure that these buildings perform well for sustainability. It will significantly value the people involved in the design, construction and also conservation practice.